Information, communication and anthropology of knowledge - DOI: 10.3395/reciis.v3i3.279en - Annette Béguin-Verbrugge (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
In Lille, ICS (Information and Communication Sciences) research revolves around the concept of anthropology of knowledge, and is strongly supported by textual sciences. Since the bond between communication and information was a core concern, the ideas of "text" or "enunciation" were used with a very broad meaning, according to a pragmatic approach that takes into consideration semiotic, social and technical contexts. At this moment of widespreadcomputerization, researchers become more centered on evolutionary rather than mediatic principles, always reaching new levels and acquiring new shapes. It is about studying the constitution, circulation and appropriation of knowledge under a perspective that is both systemic and phenomenologic.